Exploring the effects of perceived values on consumer usage intention for electric vehicle in Thailand: the mediating effect of satisfaction - Surasidh Boonchunone; Mariam Nami; Atchari Krommuang; Aphichon Phonsena; Opal Suwunnamek (Acta Logistica, 2023)
Nowadays, electric vehicle innovation plays an important role in the market, transportation, logistics and supply chain in the electric mobility industry, contributing to environmental protection and reducing pollution. The commercial EV launched in Thailand which has been very popular with consumers, but it is also not widely used, and there are not many market surveys about customer usage intention. Therefore, it is necessary to study seriously. This study explores the impact of the perceived value of electric vehicle (EV) features on consumer usage intention to use electric vehicles in Thailand, with the mediating effect of customer satisfaction. The results showed that perceived value from using EV, consumer satisfaction, and usage intention of EV, there is a significant direct and indirect relationship. These findings have contributions and relevant expected benefits.
Keywords: Electric Vehicles and Infrastructure; Advanced Battery Technologies Research; Energy, Environment, and Transportation Policies